2011
DOI: 10.1590/s0037-86822011005000006
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Mansonella ozzardi among riverine communities in the municipality of Lábrea, State of Amazonas, Brazil

Abstract: Introduction: Estimate the prevalence of Mansonella ozzardi infection and calculate the parasitic infection rate (PIR) in simuliid black flies in the municipality of Lábrea, State of Amazonas, Brazil. Methods: Prevalence was measured using the thick blood smear method collected from the fingers and was related to age, sex and occupation. Simuliidae were collected with a suction apparatus, then stained with hematoxylin and dissected to verify the PIR. Results:The average prevalence rate of M. ozzardi among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
25
3
8

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 16 publications
5
25
3
8
Order By: Relevance
“…Our data support the high prevalences (>50%) of mansonelliasis in the riverine population of Purus reported in previous studies (10) (14) . However, the rate (50.3%) of M. ozzardi infections in the present study was higher than that (20.7%) in another study conducted in the Purus River region in Lábrea that used thick blood smears (4) . In other Purus River municipalities, such as Pauini and Boca do Acre, prevalences of 24.8% and 24.1%, respectively, were previously reported (3) (14) .…”
contrasting
confidence: 90%
See 3 more Smart Citations
“…Our data support the high prevalences (>50%) of mansonelliasis in the riverine population of Purus reported in previous studies (10) (14) . However, the rate (50.3%) of M. ozzardi infections in the present study was higher than that (20.7%) in another study conducted in the Purus River region in Lábrea that used thick blood smears (4) . In other Purus River municipalities, such as Pauini and Boca do Acre, prevalences of 24.8% and 24.1%, respectively, were previously reported (3) (14) .…”
contrasting
confidence: 90%
“…The present study showed that M. ozzardi infection was present in 50.3% of the local sample, suggesting that the prevalence of this parasite in the region is higher than those recorded in recent surveys (2) (3) (4) . Furthermore, blood fi ltration using a polycarbonate membrane can be used in epidemiological surveys, especially in regions of low microfi lariae density or in post-treatment control programs, during which this method can be performed in the fi eld with minimum requirements to store blood for later analysis.…”
contrasting
confidence: 62%
See 2 more Smart Citations
“…Within the study area, there were no cases of onchocerciasis or bancroftiasis or any other Mansonella species. [8][9][10][11] The symptoms of mansonelliasis in humans have been extensively studied and persons with mansonelliasis have moderate fever, cold legs, arthralgia, and adenitis with dizziness and headache. 8,12,13 Currently, researchers are trying to correlate the occurrence of ocular lesions on the cornea with mansonelliasis.…”
Section: Introductionmentioning
confidence: 99%